A study on the application of control chart in healthcare - Seoh, Yee Kam (2019)
Measuring quality diffe is always a high priority in healthcare as bad or low quality rence in terms of patient’s life or death. A make a quality statistical technique such as statistical process control (SPC) chart monitoring s will be powerful and highly effective in process improvement and in reduc healthcare pro cess . ing the sources of variability in Control chart is statistical process control tool measure the process improvement in manufacturing that developed to industry and are recently increasingly being applied in healthcare sector. process control charts. Examples of applying statistical n monitoring the ambulance response time, medical device/equipment adverse events and number of patient safety reviewed.related dea ths are The main advantage of applying control charts methodology is control charts can determine whether the process is sta ble and to detect when significant signal or special cause of variation exist. Control charts can help healthcare institut prevent wasted investment in any changes that sound great but ion s to have no beneficial effect in real improvement. Furthermore, control charts can detect the shift in the process or significant signal from the data pattern faster than other statistical tools. More commonly, control chart can assist the healthcare institution a ppropriate or right improvement strategywhe s to select the ther to search and eliminate special causes to shift process into state of control (if process is out of control) or to put more effort on fundamental process improvement and restructure or redesign the process into desirable direction (if process is in st ate of control). When there is greater involvement of human in healthcare, the chances of error are also greater. Control chart helps to identify the source of error by differentiate the special and common cause of variation, each of which require a differ ent healthcare management response. The healthcare institution will then be aware of any abnormal behaviour or out of statistical control condition that take place in process which affected by special causes of variation and corrective or a preventive acti on could be taken immediately for eliminating the source of variation. By monitoring and supervising a process, this can ensure the process is stable, and consistently operating at its fullest potential.